[Fibrous dysplasia of the frontal sinus: a case report]. - Keleş, Erol; Kaplama, Mehmet Erkan; Ozkara, Sule; Cobano?lu, Bengü (My University, 2011)
Fibrous dysplasia is a rare and indolent benign tumor of bone. Although it is a benign tumor, it has malignant transformation potential. Fibrous dysplasia can involve a single or multiple bones. The maxilla and mandible are the most common sites in the head and neck region. Paranasal sinus involvement is rare. Surgical excision is the preferred treatment of patients with symptomatic fibrous dysplasia. In this article, a 54-year-old male patient diagnosed with fibrous dysplasia of the frontal bone is presented.
Frontal sinüste fibröz displazi: Olgu sunumu.
Keywords: Diagnosis, Differential; Fibrous Dysplasia of Bone; Frontal Bone; Humans; Male; Middle Aged; Paranasal Sinuses; article; case report; differential diagnosis; fibrous dysplasia; frontal bone; human; male; middle aged; paranasal sinus; radiography